Smooth Transparent Omniphobic Coatings with Remarkable Liquid Repellence. Issue 28 (4th September 2022) - Mayoussi, Fadoua; Chen, Yunong; Mössner, Daniela; Franco Corredor, Santiago; Goralczyk, Andreas; Mader, Markus; Warmbold, Andreas; Kotz‐Helmer, Frederik; Helmer, Dorothea; Rapp, Bastian E.
Abstract: Liquid repellent surfaces are of high interest in various fields like protective coatings and droplet manipulation due to their outstanding properties from self‐cleaning to anti‐fouling. Most reported surfaces rely on the fabrication of micro/‐nanostructured surfaces, the infusion of porous surfaces with immiscible lubricants, or the grafting of monolayers with low surface energy to achieve repellence of various liquids. However, these methods are limited in terms of their durability and long‐term stability. Here, the fabrication of smooth, transparent fluorinated poly (perfluoroalkyl methacrylate) coatings via UV‐initiated radical polymerization in a simple one‐step procedure is reported. The resulting surfaces show very low surface energies of down to 7 mN m −1, low contact angle hysteresis below 5°, very good repellence towards various liquids with different polarities as well as self‐cleaning and anti‐graffiti ability. The fabricated coatings can be applied to various substrates from glass slides to microfiber cloths. This demonstrates that they outperform common commercially available fluorinated coatings, such as, for example, Hyflon AD 40L S, in terms of liquid repellence and their performance in real‐world applications. Abstract : Facile fabrication of smooth highly repellent coatings from perfluorinated homopolymers in a simple one‐step procedure is demonstrated. The coatings show remarkable repellence towards various liquids with different surface tensions, self‐cleaning, and anti‐graffiti ability. The coatings can be directly applied to various substrates such as glass, metals, and microfiber cloths without any prior pre‐treatment.